Countering the "Democracy Thesis" – Sortition in Ancient Greek Political Theory. (1st November 2015) - Buchstein, Hubertus
Abstract : Since a decade, sortition has been experiencing a surprising and strong revival in political theory and political practice. The rediscovery of the drawing of lots has been inspired by a specific reading of the history of political ideas. According to this reading, a systematic connection between sortition and democracy already existed in ancient Greece – a point of view which I call the "democracy thesis of the lottery". The article argues that the democracy thesis of the lottery is incorrect not only with respect to the actual use of lotteries in ancient Greek poleis, but also with respect to those who theorized about this issue at that time, in particular Plato and Aristotle.